Outcomes and Complications of Bipolar vs. Monopolar Energy for Transurethral Resection of Bladder Tumors: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Mao, Xin; Zhou, Zhongbao; Cui, Yuanshan; Zhang, Yong; Yang, Mingshan (Frontiers in Surgery, 2021)
Background: Bipolar and monopolar transurethral resection have a stable status for non-muscle invasive bladder cancer (NMIBC). We conducted a meta-analysis to analyze the outcomes and complications of bipolar vs monopolar energy for transurethral resection of bladder tumors (TURB). Methods: Preferred Reporting Items for Systematic Reviews and Meta-analyses was followed. Based on the PICOS strategy, randomized controlled trials were searched in MEDLINE, EMBASE, and the Cochrane Controlled Trials Register. The reference lists of the associated articles were also retrieved. The data was calculated by Rev Man v5.3.0. Results: Eleven publications containing an amount of 2, 099 patients were involved in the study. Two groups did not show a significant difference in the mean age and the number of bladder tumors. The results showed that m-TURB had a greater decrease of postoperative hemoglobin level (Mean difference (MD) -0.26, 95% confidence interval (CI) -0.48 to -0.04, P=0.02) and sodium level (MD -0.36, 95%CI -0.62 to -0.10, P=0.007) compared with b-TURB. B-TURB spent relatively little in hospitalization time (MD -0.52, 95%CI -0.88 to -0.15, P=0.005) than m-TURB with exception of operation time (P=0.47) and catheterization time (P=0.19). B-TURB did not show a significant difference in the incidence rate of obturator reflex (P=0.10), bladder perforation (P=0.32), postoperative blood transfusion (P=0.28) and clot retention (P=0.21) compared with b-TURB group. Besides, there were no significant difference in terms of muscle tissue sampling (P=0.43), recurrence-free survival at 6-months (P=0.68) and 12-months (P=0.78). Conclusions: B-TURB was the more effective than m-TURB in minimizing intraoperative or postoperative bleeding with the smaller loss of hemoglobin and the shorter hospitalization time for patients with NMIBC.